Analisis Kasus Ujaran Kebencian Mizan Qudsiah Penghina Makam Keramat Lombok - Muhammad Faozan (STIS DAFA MATARAM, 2022)
This research aims to analyze the meaning of “hatred and inter-group relations” as described in Article 28, Section (2) of Indonesia’s Information and Electronic Transactions (ITE) Law, assessing its compliance with Indonesia’s positive legal framework, with a focus on definitional ambiguities and potential for multiple interpretations that impact legal certainty. Using a normative analysis approach, examining related articles and case studies within Indonesian jurisprudence, this study finds that the lack of clarity in the article's formulation leads to varying interpretations, particularly regarding the terms